The reception of Aesop’s fables in the Bulgarian literary and historical tradition - Walczak-Mikołajczakowa, Mariola (Balcanica Posnaniensia. Acta et studia, 2009)
The article focuses on the reception of Aesop’s fables in Bulgarian literature and the ways in which they entered the native literary and linguistic tradition. The study begins with the observation that, despite the strong ties of Bulgarian culture with the Greek-Byzantine world, Aesop’s works remained almost unknown there until the end of the eighteenth century. The aim of the paper is to present the process of adaptation of Aesopian fables in Bulgaria — from the first nineteenth-century translations to earlier, parallel forms of the genre present in the Catholic Paulician writings. The source material includes Bulgarian translations of Aesop’s fables (by Sofronius of Vratsa, an anonymous translator from 1812, Neofit Rilski, and Petko Slaveykov) as well as eighteenth-century manuscript collections of moralistic tales. The study employs philological and comparative analysis, taking into account both linguistic aspects (such as the relation to Church Slavonic, dialectal influences, and translation innovations) and literary features (didacticism, allegory, narrative structure). The author argues that the first Bulgarian translations of Aesop’s fables were based on Modern Greek adaptations and were characterized by simplified syntax and strong elements of spoken language. At the same time, even before the classical fables became known, a rich moralizing tradition already existed among Bulgarian Catholics (Paulicians), who created fables inspired by Western European models. The study concludes with a paradoxical observation: before Bulgarians encountered Aesop through translations, the moral and didactic essence of his fables had already found expression in local literature in the form of popular and religious adaptations.